The use of English among Latvian adolescents: A study of multilingual identity and language dominance - Bondare, Justīne (Taikomoji kalbotyra, 2024)
This paper examines the effects of virtual communication on language use among Latvian students aged 13-25, aiming to investigate whether language proficiency, language attitudes and identity construction are mediated by language dominance and global trends foregrounded by the dominant use of English on social media. The research material consists of 1) Bilingual Language Profile (Birdsong et al. 2012), a questionnaire that targets a variety of sociolinguistic factors and assesses language dominance; 2) a questionnaire on language use across various domains as well as language ideologies. The questionnaire results indicate Latvian language dominance in terms of language history and active use, but English is regarded as a beneficial language and used as a receptive language in entertainment and with peers. The findings of the study suggest English is associated with a multilingual identity, however, this does not seem to impact the expression of adolescents’ national identity.
Keywords: language attitudes; social identity; language dominance; multilingualism